ANALYSIS OF THE BASIC ELEMENTS OF TOURISM DESTINATION AND MARKETING POTENTIAL IN BRAJAN TOURISM VILLAGE - Ivo Novitaningtyas; Andhatu Achsa; Budi Rahardjo (Universitas Terbuka, 2019)
Tourism village is one of the tourism destinations that need to be developed. Brajan is a tourism village that has natural and cultural tourism potential. This village needs promotion in order to attract tourists. The aim of this study is to describe the basic elements of the tourism village and the marketing potential of Brajan as a tourism village. Data were collected through observation and interviews with the local communities in Brajan. After collecting the process, the data analyzed descriptively based on 6 basic elements of a tourism destination and marketing mix. The result showed that Brajan has a complete concept as a tourism destination. Moreover, this village has a lot of potential in terms of marketing. The stakeholders such as local people, manager and the Government need to developing and empowering its potential. The development of its potential is expected to have a positive impact and make the tourism village becomes a sustainable tourism destination.